2013
DOI: 10.1007/s10903-013-9846-0
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy, Acculturation, and the Use of Preventive Oral Health Care by Somali Refugees Living in Massachusetts

Abstract: Background This study investigated the impact of English health literacy and spoken proficiency and acculturation on preventive dental care use among Somali refugees in Massachusetts. Methods 439 adult Somalis in the U.S. ≤ 10 years ago were interviewed. English functional health literacy, dental word recognition, and spoken proficiency were measured using STOFHLA, REALD, and BEST Plus. Logistic regression tested associations of language measures with preventive dental care use. Results Without controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 32 publications
3
75
0
1
Order By: Relevance
“…This, coupled with the inability of refugee parents to access their traditional oral hygiene practices for example miswak, and a perceived loss of control over their children's dietary intake, contributes to the worsening levels of disease over time. This has also been reported in adult Somali refugees in the United States (Geltman et al, 2013(Geltman et al, , 2014. This young and vulnerable population requires responsive and empathetic care that includes working with their parents, families and communities.…”
Section: Discussionmentioning
confidence: 69%
“…This, coupled with the inability of refugee parents to access their traditional oral hygiene practices for example miswak, and a perceived loss of control over their children's dietary intake, contributes to the worsening levels of disease over time. This has also been reported in adult Somali refugees in the United States (Geltman et al, 2013(Geltman et al, , 2014. This young and vulnerable population requires responsive and empathetic care that includes working with their parents, families and communities.…”
Section: Discussionmentioning
confidence: 69%
“…Acculturation has a huge impact on oral health status, behaviors, and access to care, 14,15,25 which explains the significant association of poor oral health practices and lower access with care in participants who moved to the United States 1 to 2 or 2 to 5 years ago. A systematic review by Gao and McGrath showed that the higher the acculturation, better are the oral health outcomes, including oral health condition, practices, and utilization of care.…”
Section: Discussionmentioning
confidence: 99%
“…Dental diseases and cranial stress markers in modern-day Somalis who were thought to have died in the first half of the 20 th century were investigated. A literature search in the PubMed database showed that only a very small number of studies have evaluated dental disease and hygiene conditions in Somalis [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%